IMPLEMENTATION OF THE NEW MODELS OF PREPARATION OF RESEARCH ENGINEERS: A SOCIOLOGICAL ANALYSIS - Lyudmila N. Bannikova; Lyudmila N. Boronina; Yuriy R. Vishnevsky (Высшее образование в России)
The paper focuses on the problems concerning training of research engineers, summarizes the experience in implementation of new institutional forms of teaching STEM graduate and post-graduate students (STEM - Science, Technology, Engineering, Mathematics). Modern higher technical education focuses on the needs of industry. Implementation of practice-oriented bachelor programmes allows to bridge the social gap between the aspirations of graduates towards high social status and needs of the labour market for workers who can operate high-tech equipment. Skill training for modern industry actualizes the problem of training engineers for the future, for growth of the regional industry. There is a contradiction between the traditions of mass engineering education and innovative, elite training of engineers. Postgraduate and master's courses are institutional channels of recruitment and the further formation of the future engineering elite. The purpose of the article is to study the opinions, motives and career plans of the respondents who have already got basic education in engineering and make a choice for advanced engineering training, as well as to present the estimation of the training quality by the practicing engineers and employers. The findings are based on an analysis of a survey of engineers and employers of the large industrial enterprises, teachers of engineering disciplines of universities of the Ural region, masters and post-graduate students of technical institutes of the Ural Federal University.